The Emergence of Baltic Europe: An Overview of Polish Research on Regional Integration - Pacuk, Małgorzata; Palmowski, Tadeusz; Tarkowski, Maciej (Quaestiones Geographicae, 2018)
Baltic integration studies, though dispersed and involving researchers of various disciplines, generally fit well in the field of economic geography research. This article attempts to review the study results of research conducted in Poland in the last four decades. It identifies eleven leading issues, including: the Baltic wide cooperation (conditions and factors, progress and collaboration perspectives), the development of the maritime economy, international legislation, environmental protection, spatial planning and cross-border cooperation. The research focus evolved reflecting the major milestones in geopolitical transformations. In Baltic Europe we can identify three evolutionary phases: identification of cooperation paths and conditions in the competitive environment of two political and military blocks, a recast of options in the period of political transformation and European integration, studies of EU enlargement consequences.